2015
DOI: 10.1111/sms.12433
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 4 weeks of bovine colostrum supplementation on neutrophil and mucosal immune responses to prolonged cycling

Abstract: 13Bovine colostrum (COL) has been advocated as a nutritional countermeasure to 14 exercise-induced immune dysfunction. The aims of this study were to identify the 15 effects of 4 weeks of COL supplementation on neutrophil responses and mucosal 16 immunity following prolonged exercise. In a randomised double-blind, parallel group 17 design, participants (age 28 ± 8 years; body mass [BM] 79 ± 7 kg; height 182 ± 6 cm; 18 maximal oxygen uptake [ ! VO 2 max] 55 ± 9 mL·kg-1 ·min -1 ) were assigned to 20 g per 19 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(51 citation statements)
references
References 37 publications
3
48
0
Order By: Relevance
“…If there were any modulatory effects of COL on performance or stress responses, this could also contribute indirectly to effects on the immune responses. However, the present findings of similar leukocyte trafficking, and physiological measures, between groups (along with similar findings in the previous studies that also found no difference in stress hormone responses, e.g., [18,19]), suggest that subjects in this study were exposed to a matched exercise-induced stress, supporting the previous evidence that the effects of COL are not due to such indirect mechanisms.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…If there were any modulatory effects of COL on performance or stress responses, this could also contribute indirectly to effects on the immune responses. However, the present findings of similar leukocyte trafficking, and physiological measures, between groups (along with similar findings in the previous studies that also found no difference in stress hormone responses, e.g., [18,19]), suggest that subjects in this study were exposed to a matched exercise-induced stress, supporting the previous evidence that the effects of COL are not due to such indirect mechanisms.…”
Section: Discussionsupporting
confidence: 92%
“…The mechanism(s) behind such effects remain unclear, but it has been proposed that it is linked to COL reducing perturbations in cellular immunity following prolonged exercise [17]. We have previously demonstrated that COL blunts the decrease in blood neutrophil effector functions following prolonged exercise [18,19]. Shing et al [20] observed a prevention of a post-exercise decrease in cytotoxic/suppressor T cells during an intensive period of training.…”
Section: Introductionmentioning
confidence: 93%
“…As described previously [21], neutrophil phorbol-12-myristate-13-acetate (PMA)- and formyl-methionyl-leucyl-phenylalanine(fMLP)-stimulated oxidative burst were assessed by a chemiluminescence (CL) kit (ABEL ® 04 M, Knight Scientific Ltd, Plymouth, UK) incorporating the light-emitting protein Pholasin ® . The CL per well was measured by a microplate luminometer (FLUOstar OPTIMA, BMG Labtech, Aylesbury, UK).…”
Section: Methodsmentioning
confidence: 99%
“…For fMLP, CL was recorded every second for 300 s. The area under the unstimulated CL curves was subtracted from stimulated curves of the same sample to determine PMA- or fMLP-stimulated oxidative burst. To calculate responses on a per-cell basis in whole blood, area under the CL curve was expressed as the number of neutrophils (in well) only as the contributions of monocytes, eosinophils and basophils in our 1:1010 final dilution of blood are considered to be insignificant [21, 22]. …”
Section: Methodsmentioning
confidence: 99%
“…Other researchers have identiied improvements in disorders such as obesity, insulin resistance, leaky gut syndrome, and ulcers [62,63]. Colostrum supplementation has helped to improve performance in horses by its apparent ability to stimulate neutrophil's oxidative response following prolonged exercise [64].…”
Section: Super Foods and Functional Food For Horsesmentioning
confidence: 99%